PEMANFAATAN BATU â€œAPEâ€œ DARI SUNGAI LUA KABUPATEN KEPULAUAN TALAUD SEBAGAI ALTERNATIF BAHAN BANGUNAN - Pongajow, Gerson; Satyarno, Iman; Tjokrodimuljo, Kardiyono (Civil Engineering Forum Teknik Sipil, 2008)
Talaud Archipelago Sub-Province is one of the Sub-Provinces in North Sulawesi Province, the growing result of Sangihe and Talaud Archipelago Sub-Province in 2002. This growth followed by the development in all fields, including the infrastructure development which is based stone from outside of the island. This research is done to explore the local potential and also to test laboratory that the local stone can be used as alternative construction materials. In this study, there are 85 stone cube which are used to test itâ€™s strength. Each variant of test is 5 stone and the factor will be given to the stone is the temperature which is 200oC, 400oC, 600oC and 800oC in 15, 30, 60 and 120 minutes. And then follow by checking the rout aggregate nature. Next step is to make concrete which is made by the mix of the aggregate of â€œApeâ€ stone and the sand from River Lua Talaud Archipelago and also concrete which is used the mix of the â€œApeâ€ stone aggregate and the sand from mount Merapi in Yogjakarta. The result shows that the heat of â€œApeâ€ stone can increase the strength of the stone. In the beginning, the strngth is 6,052 MPa., and then maximum increase until 37,43 MPa., after been heated in 400oC temperature for 120 minutes. The aggregate of theâ€œApeâ€ stone which is been heated includes the lightweight aggregate which can be used directly as an alternative of Red Stone. Concrete as the mix of the â€œApeâ€ stone which is heated before, and the sand from Lua River with fas of value 0,5 and 410 kg/m3 cement weight. the weight of ratio concrete 2, 04 kg/dm3 and strength 12, 88 MPa, and also concrete which is mix by the â€œApeâ€ stone and the merapi mount sand with fas of value 0,5 and 410 kg/m3 cement weight, the weight of ratio concrete 2,12 kg/dm3 and strength 15,79 MPa. Result, the concrete is the lightweight concrete with the B0 and B1 class. So the conclusion is the â€œApeâ€ stone, can be use as an alternative of construction material.